The efficacy of a Mindfulness Based Intervention for depressive symptoms in patients with Multiple Sclerosis and their caregivers: study protocol for a randomized controlled clinical trial. Issue 1 (December 2016) - Carletto, Sara; Borghi, Martina; Francone, Diana; Scavelli, Francesco; Bertino, Gabriella; Cavallo, Marco; Malucchi, Simona; Bertolotto, Antonio; Oliva, Francesco; Ostacoli, Luca
Abstract Background Multiple Sclerosis has a great impact on psychological functioning of patients and can be associated with various mental health disorders and symptoms. The most prevalent one is depression, which ranges from 15 to 47 %. Mindfulness Based Interventions are a relatively brief and cost-effective program that has been studied in patients with several chronic diseases and recently also in patients with Multiple Sclerosis. Mindfulness Based Interventions are based on the assumption that a non-judgmental awareness and acceptance of one's moment-to-moment experience can have a positive effect on the adaptation to the disease, reducing the psychological burden and improving patients' quality of life. Several studies concluded that Mindfulness Based Interventions can be beneficial in terms of improving both psychological and psychical aspects of Multiple Sclerosis, but none of them compared the intervention with an active control group. The primary objective of the study is to evaluate the efficacy of a group-based Mindfulness Based Intervention on depressive symptoms in patients with Multiple Sclerosis, as compared with an active control group. Methods The study design is a randomized controlled clinical trial. Eighty-eight patients with Multiple Sclerosis and depressive symptoms will be recruited and randomized to either Mindfulness Based Intervention or an active control group. The latter is designed to control for non-specific elements of the intervention and it comprises psycho-education and relaxation techniques. The primary outcome is the reduction of depressive symptoms as measured via the Beck Depressive Inventory-II. Secondary outcome measures are level of quality of life, anxiety, perceived stress, illness perception, fatigue and quality of interpersonal relationship. Outcomes will be assessed at baseline, after treatment and 6 months after the end of the treatment. Caregivers will participate in groups together with patients. Discussion As far as we know this trial will be the first randomized controlled trial testing the efficacy of group-based Mindfulness Based Intervention for patients with Multiple Sclerosis with a comparison with an active control group with a specific focus on depressive symptoms. Trial registration NCT02611401 .